An era of flux fluidity in the Regional Maritime Environment - Ho, Joshua (2016)
AT no time since the formation of the Western alliance system in 1949 have the shape and nature of international alignments been in such a state of flux. The end of the Cold War shifted the tectonic plates, but the repercussions from these momentous events are still unfolding. Emerging powers in Asia, a dramatic reduction in the possibility of inter-state conflict in Europe, a troubled Middle East, and transatlantic divisions are among the issues that have only come to a head in recent years. The very magnitude and speed of change resulting from a globalising world will be a defining feature of the world in the future.